Ionospheric F-region currents estimated from Macau Science Satellite-1 and Swarm satellite magnetic data - JuYuan Xu; HongBo Yao; Keke Zhang (Earth and Planetary Physics)
Accurate modeling of Earth’s ionospheric F-region currents is essential for refining geomagnetic field models and understanding magnetosphere-ionosphere coupling. In this study, we develop averaged models to characterize F-region currents using magnetic data from the MSS-1 (Macau Science Satellite-1) and Swarm satellite missions. Our approach employs a toroidal field representation, utilizing spherical harmonics to capture spatial variations and Fourier series to represent temporal dynamics. Two models, Model-A and Model-B, derived from distinct datasets, are constructed to represent current patterns at altitudes of 450 km and 512 km, respectively. Our models successfully capture the primary spatial structures and seasonal variations of polar field-aligned currents. Additionally, they accurately reproduce the localized inter-hemispheric field-aligned currents observed in mid and low latitudes during solstices, particularly between 14:00 and 16:00 magnetic local times. These findings enhance our understanding of ionospheric F-region currents and contribute to more precise geomagnetic field modeling.